Risk Perceptions and Risk Management in International Environmental Cooperation Projects in Russia : Case Krasny Bor - Rajala, Karoliina (My University, 2020)
This study explores risk perceptions and risk management in international environmental projects. The topic is examined via the use of a case study that focuses on a project surrounding the remediation of the Krasny Bor waste site. The aim of the study is to obtain an enhanced understanding of the differences in risk perceptions of key actors in international environmental projects and suggest which risk management techniques could be applied to ensure successful completion of international environmental cooperation projects. Finally, the study is interested in exploring which insights from the case study can be applied to future environmental cooperation in Russia. The data of the study was collected via semi-structured interviews. After this thematic content analysis was applied to the results. First, the results were coded and after that grouped and analyzed. Analysis focused on two key topics, the risk perceptions of project actors and risk management techniques proposed by project actors. The study notes that that the main risks that the project actors identified in the Krasny Bor project were of financial, legal, political, technical and institutional nature. It was noted that even though many of the project actors brought up the same risks, there still existed differences in risk perceptions. Meanwhile, the main techniques that were proposed for facilitating project success included upholding political attention on the project both in Russia and abroad. However, the international project actors believe that otherwise there are limited methods for them to manage risk and instead risk management responsibility should be taken more by the Russian side.

Tässä tutkimuksessa tarkastellaan riskinäkemyksiä ja riskienhallintaa kansainvälisissä ympäristöhankkeissa. Aihetta tarkastellaan tapaustutkimuksen avulla, joka keskittyy Krasnyi Borin ongelmajätekaatopaikan kunnostamiseen liittyvään projektiin. Tutkimuksen tavoitteena on luoda ymmärrystä eroista kansainvälisten ympäristöhankkeiden avaintoimijoiden riskinäkemyksissä ja tuoda esille riskinhallintatekniikoita, joita voitaisiin soveltaa kansainvälisissä ympäristöyhteistyöhankkeissa. Tutkimuksen avulla koitetaan selvittää, mitä tapaustutkimuksesta saatuja näkemyksiä voitaisiin soveltaa tulevaisuuden ympäristöyhteistyöhön Venäjällä. Tutkimuksen empiria kerättiin haastattelujen avulla, minkä jälkeen temaattista sisältöanalyysia hyödynnettiin tulosten analysoimisessa. Empiria koodattiin, ryhmiteltiin ja analysoitiin. Analyysi keskittyi kahteen teemaan: projektitoimijoiden riskinäkemyksiin ja heidän ehdottamiin riskienhallintatekniikkoihin. Tutkimuksessa todetaan, että Krasnyi Borin hankkeeseen liittyvät riskit voidaan jaotella luonteeltaan taloudellisiin, oikeudellisiin, poliittisiin, teknisiin ja institutionaalisiin. Vaikka monet projektitoimijat toivat esille myös samoja riskejä, heidän riskinäkemyksissään voidaan todeta olleen myös olennaisia eroja. Tutkimustulokset osoittavat, että projektitoimijoiden mielestä paras riskienhallintakeino kansainvälisissä ympäristöyhteistyöhankkeissa Venäjällä on poliittisen huomion ylläpitäminen niissä sekä Venäjällä että ulkomailla. Lisäksi kansainväliset projektitoimijat uskovat, että heidän keinonsa riskienhallinnassa ovat rajalliset ja sen sijaan riskienhallinnan päävastuun pitäisi olla venäläisillä toimijoilla.
Keywords: project risk, risk perception, risk management, environmental cooperation, projektiriski, riskinäkemys, riskienhallinta, ympäristöyhteistyö